Analisis Rasio Keuangan Untuk Menilai Kinerja Keuangan Pada Perusahaan Multifinance Yang Terdaftar Di Bursa Efek Indonesia Periode Tahun 2015-2019 - Turmono; Mawarto (Coopetition : Jurnal Ilmiah Manajemen, 2021)
The objective of this research is to know the best financial performance and the financial performance ratio of multifinance companies listed at Indonesian Stock Exchange reviewed from the analysis of liquidity ratio, solvency ratio, activity ratio and profitability ratio. The method applied is descriptive and comparative methods. The result based on comparative method the ratio in 5 years calculated by the liquidity ratio of the company having the best CR is CFIN because it has the highest ratio of 230.15% and the best CSR is WOMF by 13.44%. The best solvency ratio is CFIN with the lowest DAR and DER ratio is 55.9% and 126.93%. Activity ratio result indicates the best RTO value is WOMF because it has the highest ratio by 0.37 times and the best TATO is ADMF with highest ratio of 0.32 times. The best profitability ratio is achieved by ADMF because it has the highest ROA and ROE ratios of 4.62% and 23.21%. Of total score in 2015-2019 periods, the first rank is occupied by ADMF with score 64, CFIN in the second one with score 84 and WOMF in the third with score 92.